2022
DOI: 10.3390/nu14122367
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Path of Mediterranean Diet, Non-Alcoholic Fatty Liver Disease (NAFLD) and Inflammation towards 10-Year Cardiovascular Disease (CVD) Risk: The ATTICA Study 10-Year Follow-Up (2002–2012)

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is the leading cause of liver disease, affecting ~30% of the population and increasing CVD. This study aimed to explore the direct, indirect and combined effects of Mediterranean diet, NAFLD and inflammation on the 10-year CVD risk in a healthy adult population. Methods: Using baseline and 10-year follow-up data from the ATTICA study, adherence to Mediterranean diet was measured using MedDietScore, and presence of NAFLD at baseline was assessed using the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Rey Auditory Verbal Learning Test (RAVLT; 95,138,139). We will administer the RAVLT to assess cognitive bene ts of both interventions, given that both interventions are expected to improve in ammation (140)(141)(142)(143)(144)(145) and that in ammation has been shown to be related to cognitive performance for those with BD (146-148). This test has been shown to be sensitive to cognitive de cits associated with BD, even during euthymic periods (149,150).…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…Rey Auditory Verbal Learning Test (RAVLT; 95,138,139). We will administer the RAVLT to assess cognitive bene ts of both interventions, given that both interventions are expected to improve in ammation (140)(141)(142)(143)(144)(145) and that in ammation has been shown to be related to cognitive performance for those with BD (146-148). This test has been shown to be sensitive to cognitive de cits associated with BD, even during euthymic periods (149,150).…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…Rey Auditory Verbal Learning Test (RAVLT; [92,93,125]). We will administer the RAVLT to assess cognitive benefits of both interventions, given that both interventions are expected to improve inflammation [126][127][128][129][130][131] and that inflammation has been shown to be related to cognitive performance for those with BD [132][133][134]. This test has been shown to be sensitive to cognitive deficits associated with BD, even during euthymic periods [135,136].…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…However, a recent randomised controlled trial showed no clinically significant differences between the Mediterranean diet and a low-fat diet [ 214 ]. Despite this, given the Mediterranean diet is shown to improve cardiovascular outcomes [ 215 , 216 ], recommendations to follow a Mediterranean-like diet in NAFLD remain reasonable.…”
Section: Treatment Optionsmentioning
confidence: 99%